Characterization of fliR-deletion mutant ΔfliR from Vibrio alginolyticus and the evaluation as a live attenuated vaccine - Da, Fan; Wan, Xiaoju; Lin, Guixiang; Jian, Jichang; Cai, Shuanghu (Frontiers in Cellular and Infection Microbiology, 2023)
Vibrio alginolyticus is the common pathogen affecting various species of marine organisms. It has been demonstrated that fliR is a necessary virulence factor to adhere and infect their hosts for pathogenic bacteria. Frequent disease outbreaks in aquaculture have highlighted the necessity of developing effective vaccines. In the present study, in order to investigate the function of fliR in V.alginolyticus, the fliR deletion mutant ΔfliR was constructed and its biological properties were evaluated, additionally, the differences in gene expression levels between wild-type and ΔfliR were analyzed by transcriptomics. Finally, ΔfliR was used as a live attenuated vaccine to immunize grouper via the intraperitoneal route to evaluate its protective effect. Results show that fliR gene of V. alginolyticus was identified as being 783 bp in length, encoding 260 amino acids, and showing significant similarity to homologs of other Vibrio species. The fliR-deletion mutant ΔfliR of V. alginolyticus was successfully constructed, and its biological phenotype analysis showed no significant differences in growth capacity and extracellular enzyme activity compared to the wild-type. However, a substantial reduction of motility ability was detected in ΔfliR. Transcriptomic analysis revealed that the absence of fliR gene is responsible for a significantly decreased expression of flagellar genes, including flaA, flaB, fliS, flhB and fliM. The fliR-deletion mainly affects the related pathways involved in cell motility, membrane transport, signal transduction, carbohydrate metabolism, and amino acid metabolism in V. alginolyticus. The efficacy of ΔfliR as a candidate of live attenuated vaccine were evaluated by intraperitoneal injection in grouper. The ΔfliR provided the RPS (Relative protection rate) of 67.2% against V. alginolyticus in groupers. The ΔfliR efficiently stimulated antibody production with specific IgM still detected at 42 d post-vaccination, and significantly elevated the activity of antioxidant enzymes like Catalase (CAT), Superoxide dismutase (SOD), and lactate dehydrogenase (LDH) in the serum. The higher expression levels of immune-related genes were observed in the immune tissues of inoculated grouper compared to the control. In conclusion, ΔfliR effectively improved the immunity of inoculated fish. The results suggest that ΔfliR is an effective live attenuated vaccine against vibriosis in in grouper.